Persistence of Supplemented Bifidobacterium longum subsp. infantis EVC001 in Breastfed Infants - Steven A. Frese (American Society for Microbiology, 2017)
ABSTRACT Attempts to alter intestinal dysbiosis via administration of probiotics have consistently shown that colonization with the administered microbes is transient. This study sought to determine whether provision of an initial course of Bifidobacterium longum subsp. infantis (B. infantis) would lead to persistent colonization of the probiotic organism in breastfed infants. Mothers intending to breastfeed were recruited and provided with lactation support. One group of mothers fed B. infantis EVC001 to their infants from day 7 to day 28 of life (n = 34), and the second group did not administer any probiotic (n = 32). Fecal samples were collected during the first 60 postnatal days in both groups. Fecal samples were assessed by 16S rRNA gene sequencing, quantitative PCR, mass spectrometry, and endotoxin measurement. B. infantis-fed infants had significantly higher populations of fecal Bifidobacteriaceae, in particular B. infantis, while EVC001 was fed, and this difference persisted more than 30 days after EVC001 supplementation ceased. Fecal milk oligosaccharides were significantly lower in B. infantis EVC001-fed infants, demonstrating higher consumption of human milk oligosaccharides by B. infantis EVC001. Concentrations of acetate and lactate were significantly higher and fecal pH was significantly lower in infants fed EVC001, demonstrating alterations in intestinal fermentation. Infants colonized by Bifidobacteriaceae at high levels had 4-fold-lower fecal endotoxin levels, consistent with observed lower levels of Gram-negative Proteobacteria and Bacteroidetes. IMPORTANCE The gut microbiome in early life plays an important role for long-term health and is shaped in large part by diet. Probiotics may contribute to improvements in health, but they have not been shown to alter the community composition of the gut microbiome. Here, we found that breastfed infants could be stably colonized at high levels by provision of B. infantis EVC001, with significant changes to the overall microbiome composition persisting more than a month later, whether the infants were born vaginally or by caesarean section. This observation is consistent with previous studies demonstrating the capacity of this subspecies to utilize human milk glycans as a nutrient and underscores the importance of pairing a probiotic organism with a specific substrate. Colonization by B. infantis EVC001 resulted in significant changes to fecal microbiome composition and was associated with improvements in fecal biochemistry. The combination of human milk and an infant-associated Bifidobacterium sp. shows, for the first time, that durable changes to the human gut microbiome are possible and are associated with improved gut function.